Susceptibility of Shy Students to Internet Addiction: A Multiple Mediation Model Involving Chinese Middle-School Students - Yu, Yang; Sun, Hong; Gao, Fengqiang (Frontiers in Psychology, 2019)
Recent studies found that some personality traits (e.g., impulsivity, sensation seeking) are frequently related to Internet addiction. In line with previous studies, this study aimed to determine whether shy students readily develop Internet addiction and to identify the causes of their developing Internet addiction. Specifically, this study examined the mediating roles of cognitive flexibility, self-regulation, and self-inconsistency in linking shyness and Internet addiction. A total of 1301 middle-school students in Shandong Province, East China, completed the relevant scales. Correlation analysis revealed that shyness was positively correlated with self-inconsistency and Internet addiction and negatively correlated with self-regulation and self-inconsistency. Cognitive flexibility, self-regulation, and self-inconsistency played fully mediating roles in the relationship between shyness and Internet addiction. The results indicate the significance of shyness-sensitivity for Internet addiction and suggest that cognitive and coping abilities as well as social adjustment factors should be considered when designing interventions to help shy students overcome Internet addiction.